2018
DOI: 10.1016/j.ebiom.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

LDL Receptor Gene-ablated Hamsters: A Rodent Model of Familial Hypercholesterolemia With Dominant Inheritance and Diet-induced Coronary Atherosclerosis

Abstract: Familial hypercholesterolemia (FH) is an autosomal dominant genetic disease caused mainly by LDL receptor (Ldlr) gene mutations. Unlike FH patients, heterozygous Ldlr knockout (KO) mice do not show a dominant FH trait. Hamsters, like humans, have the cholesteryl ester transfer protein, intestine-only ApoB editing and low hepatic cholesterol synthesis. Here, we generated Ldlr-ablated hamsters using CRISPR/Cas9 technology. Homozygous Ldlr KO hamsters on a chow diet developed hypercholesterolemia with LDL as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 28 publications
7
64
1
Order By: Relevance
“…Given that this study was performed in the animal model lacking LDLR, these data may be more relevant for humans with familial hypercholesterolemia than for general population. As previously reported by Guo et al, high-fat diet can induce human-like hyperlipidemia in LDLR −/− hamsters [17]. The TC-lowering effect of ezetimibe was consistent with the results obtained from C57BL/6 J mice [13], apolipoprotein E knockout mice [24], rhesus monkeys [6], and humans [10].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Given that this study was performed in the animal model lacking LDLR, these data may be more relevant for humans with familial hypercholesterolemia than for general population. As previously reported by Guo et al, high-fat diet can induce human-like hyperlipidemia in LDLR −/− hamsters [17]. The TC-lowering effect of ezetimibe was consistent with the results obtained from C57BL/6 J mice [13], apolipoprotein E knockout mice [24], rhesus monkeys [6], and humans [10].…”
Section: Discussionsupporting
confidence: 91%
“…The TG-lowering effect of ezetimibe in LDLR −/− hamsters was inconsistent with the data in rhesus monkeys [6], and humans [10]. However, our data were consistent with the previous results obtained in LDLR −/− animals [17,19], which also indicated that ezetimibe not only significantly reduced plasma TC levels but also decreased plasma TG levels. These differences may be attributed to the distinct animal models, and especially the absent of LDLR.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This result could be attributed to the inability of traditional machine learning to extract deeper abstract features for prediction, resulting in poor performance, while DLDTI applies a deep convolutional neural network approach and is able to capture the potential structural properties of complex networks and heterogeneous information.Furthermore, in the validation study of the DLDTI model, we used TMPZ (a drug with known structure) to explore its effects on atherosclerosis in vivo. Consistent with previous studies[16][17][18], the results revealed that TMPZ could ameliorate the phenotyping of atherosclerosis in Ldlr-/-hamsters, a novel atherosclerosis model[31][43]. Diminished lipid deposition and macrophage accumulation, and increased percentage of SMC were observed in TMPZ-and clopidogrel-treated hamsters.…”
supporting
confidence: 91%
“…Like humans but unlike like mice, rabbits have abundant plasma cholesteryl ester transfer protein (CETP) activity, intestine-only ApoB mRNA editing, considerable hepatic cholesterol synthesis, and LDL as predominate plasma lipoprotein, and other traits [ 49 , 57 , 58 ]. It is generally better to use an animal model with lipid metabolism mechanisms similar to that of humans.…”
Section: Discussionmentioning
confidence: 99%